Design of educational software based on skill development (Revista de Investigaciones Universidad del Quindío, 2009)
This article describes an educational software design model based on skills development, which presents a vision of developing these applications by combining components of teaching, learning, multimedia and software engineering. The suggested model consists of five stages that describe the steps to be taken into account for the creation of educational software. The initial phase is the description of education design, which analyzes the educational need, outlines the learning objectives, and summarizes the skills that the application look forward to develop. From the design of these aspects, the following sub-phases are developed: content design, pedagogical design and learning design. Skills are the key point that involves the development of this model, which are essential for carrying out the steps to follow the computational design and multimedia design; these are responsible for the analysis and software modeling, and for the man-machine communication system. In the production phase are assembled the components produced or collected, as appropriate. The last phase is implementation, where tests are applied to evaluate the rigor of the software in the contexts for which it was developed.
Keywords: Educational software; software engineering; education; computing; skills